Referenciação na construção de sentidos em reportagens de popularizaçao da ciência sobre a Covid-19 - Bernardi, Eviliane (2023)
The objective of this research is to investigate how the referential process established by direct anaphoras constituted by lexical resources and by (re)formulation procedures contributes to the recontextualization of scientific discourse and the construction of meanings in science popularization reports on Covid-19. The corpus consists of ten science popularization reports on the topic of Covid-19, published in the journal Pesquisa FAPESP, between March 2020 and March 2021. The objective is to verify the occurrences of direct anaphoras constituted by lexical resources in the (re)construction of discourse objects related to Covid-19 and the most representative occurrences of the (re)formulation procedures in the construction of the reference established by Zamponi (2005) and their discursive functions: metaphorical expressions; exemplifications; definitional and didactic anaphoras; and appositions. This research is qualitative with an analytical-descriptive and interpretive bias. It focuses on the sociocognitive and interactionist perspective of the phenomenon of reference, according to theoretical guidelines of Text Linguistics. To support the analyses, this research is anchored in studies that consider reference as a discursive activity of construction and reconstruction of discourse objects, which are constituted in discourse and interactively conceived, according to the sociocognitive and interactionist bias, as Mondada and Dubois (2003), Apothéloz and Reichler-Béguelin (1995), Koch (2002, 2005, 2006a, 2006b, 2008a, 2008b, 2008c, 2008d), Marcuschi (2005, 2007), Schwarz-Friesel (2007), Zamponi (2005), Apothéloz (2003), Cavalcante (2003, 2015, 2016), among others. The results indicate that, due to the historical-political-social context in which the Covid-19 pandemic is situated, both in Brazil and worldwide, characterized by polarizations regarding the disease, its treatment, vaccines and science itself, the re-elabortion of discourse objects through direct anaphoras by lexical resources and the occurrence of (re)formulation procedures in science popularization reports indicate not only the objective of making scientific information less abstract, but also the objective of persuading the reader, whether to capture the reader's attention, guide behavior or shape attitudes.